Exploring the Perceptions of Employees on the Impact of Gender in Leadership Positions: An Assessment of Employees in Local Authorities in Zimbabwe - Mlambo, Aleck (European Journal of Applied Sciences, 2024)
The topic of leadership has been addressed and applied for many years but the concept of gender in leadership positions was not given thorough assessment in various spheres of research. The main purpose of this study was to establish the perceptions of employees on the impact of gender in leadership positions. Literature review on leadershippositions was discussed. The study focussed on leadership styles, communication, emotional intelligence, employees’ performance, and gender in leadership positions. The topic of gender and leadership deserves serious discussion because of its professional, political, economic, cultural, and personal realities of the twenty first century. The study used the qualitative and quantitative methods of conducting the research and the questionnaire was found to be an appropriate instrument to collect data. The target population was composed of 100 employees and a sample of 50 participants were used to gather data for the study. Data was presented in forms of graphs, tables and pie charts which made it easier to analyse and interpret the results using SPSS. The results and findings revealed that men and women were the same. The findings also revealed that leadership positons had nothing to do with gender. The results also showed that men looked down upon women in leadership positions. The results also proved that emotional intelligence had nothing to do with gender. It was the goal of this research that NGOs, government institutions, private and public organisations and beyond the globe benefit from this study.